THE CONCEPT OF WELL-BEING IN SCHOOL REFLECTED IN EUROPEAN AND INTERNATIONAL DOCUMENTS - Florentina MOGONEA (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2025)
Maintaining well-being in school is a current priority, because a stimulating, open learning environment is an important condition for the efficiency of a certain activity. The present study aims to carry out a critical analysis of the concept of wellbeing in school, as it is reflected in European and international documents, which show interest in this aspect. What are the conditions, the factors that influence well-being, what are the pillars it is built on, what methods prove to be more effective in ensuring the wellbeing of students, teachers and all those involved in school activity are the essential questions that formed the basis of this investigation, based on the study and critical analysis of certain documents and reports drawn up by important European and international bodies (OECD, European Commission, UNICEF, World Health Organization). All these pursued aspects are intended to ensure a more complex and realistic perspective on the concept, allowing a better delimitation of the notional sphere. The conclusions drawn may be useful to all those responsible for ensuring the well-being of the important school "actors".